Dopaminergic and glutamatergic biomarkers disruption in addiction and regulation by exercise: a mini review. (19th May 2022) - Abdullah, Muhammad; Huang, Li-Chung; Lin, Shih-Hsien; Yang, Yen Kuang
Abstract: Introduction: Drug addiction is associated with disruption of a multitude of biomarkers in various brain regions, particularly in the reward centre. The most pronounced are dopaminergic and glutamatergic biomarkers, which are affected at various levels. Neuropathological changes in biomarkers alter the homeostasis of the glutamatergic and dopaminergic nervous systems and promote addiction-associated characteristics such as repeated intake, maintenance, withdrawal, reinstatement, and relapse. Exercise has been shown to have a buffering effect on such biomarkers and reverse the effects of addictive substances. Methods: A review of the literature searched in PubMed, examining drug addiction and physical exercise in relation to dopaminergic and glutamatergic systems at any of the three biomarker levels (i.e. neurotransmitter, receptor, or transporter). Results: We review the collective impact of addictive substances on the dopaminergic and glutamatergic systems and the beneficial effect of exercise in terms of reversing the damage to these systems. We propose future directions, including implications of exercise as an add-on therapy, substance use disorder (SUD) prognosis and diagnosis and designing of optimised exercise and pharmaceutical regimens based on the aforementioned biomarkers. Conclusion: Exercise is beneficial for all types of drug addiction at all stages, by reversing molecular damages caused to dopaminergic and glutamatergic systems.